The Road Not Taken: Building Physics, and Returning to First Principles in Sustainable Design - Robyn Pender; Daniel J. Lemieux (Atmosphere, 2020)
The path we are currently following towards ‘sustainable design’ is a result of the accidents of the past 300 years of history. If we look further back, to before the exploitation of fossil fuels, we find a very different approach to building envelopes, and to building use and comfort. This was necessarily very low carbon, and demonstrably effective, but, unfortunately, we have forgotten many of the fundamental principles on which it rested. This paper argues that our current choice of retrofit pathway is leading us away from, rather than towards, a sustainable built environment. Current efforts to reduce carbon and energy based on modern ’layered’ envelopes and misunderstandings of thermal comfort are proving much less effective than predicted. We would further argue that they are too often delivering unintended consequences: contributing to the overuse of carbon and energy, and derailing the development of a sustainable built environment. We draw on research and case studies, as well as on the lessons from history, to show how the problem derives from a neglect of first-principles thinking and fundamental building physics. Equally, though, we show how combining good building physics with a re-evaluation of older approaches to construction and building use delivers some powerful and effective tools for tackling the climate emergency.